2020
DOI: 10.1139/cjfas-2019-0037
|View full text |Cite
|
Sign up to set email alerts
|

State-space modeling of multidecadal mark–recapture data reveals low adult dispersal in a nursery-dependent fish metapopulation

Abstract: Quantifying connectivity within fish metapopulations is an important component in understanding population dynamics and providing an evidence base for assessment and management. We investigate metapopulation connectivity of the common sole (Solea solea) in the Eastern English Channel (EEC). The EEC common sole stock is currently assessed as a single and spatially homogeneous population, but connectivity induced through adult movements within this stock and with nearby stocks remains unknown. To fill this knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 83 publications
(102 reference statements)
0
16
0
Order By: Relevance
“…First, the connection between subunits could have been stronger in 2018. This explanation is unlikely since a mark-recapture study has suggested low adult movement across the EEC over decades [ 22 ], which is in line with the spatial genetic pattern found in 2017. Second, the observed differences could be due to a library effect.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…First, the connection between subunits could have been stronger in 2018. This explanation is unlikely since a mark-recapture study has suggested low adult movement across the EEC over decades [ 22 ], which is in line with the spatial genetic pattern found in 2017. Second, the observed differences could be due to a library effect.…”
Section: Discussionmentioning
confidence: 76%
“…Based on the EEC underwater topography and the results of the biophysical modelling [ 53 ], a functioning in three subunits have been hypothesized ( Fig 1 ). Life history traits at the population scale supported the spatial structure in three putative subunits ([ 59 , 60 ]; Fig 1 ) and mark-recapture experiments estimated low exchanges between these subunits ([ 22 ]; Fig 1 ). However, the population structure has not been investigated yet at the individual level, nor a potential genetic differentiation.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations